(3Odjd GdQSGFd hGdCWQhMGJ GdLGeYjI HGdeZQH aj eLGd GdOQGSGJ GdbQBfjI (B:s (3LQO HHdjhZQGaj hJUfja ehVhYj, hJbjje (B= Index of papers and university thesises in Morocco in the field of Quranic studies : Bibliographical inventory, objective classification and assessment /s - (3GdfGUQj, aGWeI GdRgQGAs (a, 2018)
(3gPG GdcJGH Odjd GdQSGFd hGdCWQhMGJ GdLGeYjI HGdeZQH aj eLGd GdOQGSGJ GdbQBfjI gh CMO GdLghO GdEMUGFjI hGdJj JYO NWhI egeI dQUO hGbY GdOQS GdbQBfj bWQjG hYQHjG jJLGhR eLQO GdEMUGA GdejcGfjcj GdNOeGJj Edi EMUGA hXjaj jbOe eDTQGJ efgLjI egeI hPdc dMVhQ GdJUfja GdeYQaj hGdehVhYGJj ddQSGFd hgh GdgGLS GdefgLj MJi jJSfi dgPG GdOdjd Cf jbhe HJhVjM GdQDjI Mhd SjQ GdOQS GdbQBfj HGdeDSSGJ GdLGeYjI(B. s
Keywords: (3GdbQBfs -- (3Ydhes -- (3HHdjhLQGajGJs; (3COdIs -- (3GdeZQHs -- (3HHdjhLQGajGJs -- (3Ydhe GdbQBfs -- (3GdQSGFd GdLGeYjIs